2020
DOI: 10.1177/1077558720903882
|View full text |Cite
|
Sign up to set email alerts
|

Care Continuity and Care Coordination: A Preliminary Examination of Their Effects on Hospitalization

Abstract: Both care continuity and care coordination are important features of the health care system. However, little is known about the relationship between care continuity and care coordination, their effects on hospitalizations, and whether these effects vary across patients with various levels of comorbidity. This study employed a panel study design with a 3-year follow-up from 2007 to 2011 in Taiwan’s universal health coverage system. Patients aged 18 years or older who were newly diagnosed with diabetes in 2007 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
(140 reference statements)
1
8
0
Order By: Relevance
“…Patients with perfect provider COCI (provider COCI=1) had lower utilization of ICU: OR=0.78, CI: 0.67-0.90. Patients with perfect site COCI had an OR of 0.74 (CI:0.67-0.83) in the utilization of the ER Chen 2020b; Taiwan [ 48 ] RC To examine the relationship between COC and care coordination, simultaneously evaluate the effects of COC and care coordination on healthcare outcomes, and investigate whether these effects vary across study subjects with different levels of comorbidity Longitudinal Cohort of Diabetes Patients claims data sets constructed by the National Health Research Institute in Taiwan 57,965 patients aged 18 years or older who were newly diagnosed with diabetes 2007-2011 COCI, Care density 8/9 Each year of 3 years follow-up Partly, reversed causality accounted in design and discussed in limitations Hospital admission for diabetes or cardiovascular/cerebrovascular conditions Multi-morbid patients with high- or median-COCI were less likely to be hospitalized for diabetes-related conditions than those in the low-continuity group (OR=0.86, CI: 0.77- 0.96) and (OR=0.90, CI: 0.83-0.98), respectively. For care coordination, the patients in the high- or median-care-density groups were less likely to be hospitalized for diabetes-related conditions than the patients in the low-care-density group (OR=0.84, CI: 0.76-0.93, and OR=0.91, CI:0.84-0.99).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with perfect provider COCI (provider COCI=1) had lower utilization of ICU: OR=0.78, CI: 0.67-0.90. Patients with perfect site COCI had an OR of 0.74 (CI:0.67-0.83) in the utilization of the ER Chen 2020b; Taiwan [ 48 ] RC To examine the relationship between COC and care coordination, simultaneously evaluate the effects of COC and care coordination on healthcare outcomes, and investigate whether these effects vary across study subjects with different levels of comorbidity Longitudinal Cohort of Diabetes Patients claims data sets constructed by the National Health Research Institute in Taiwan 57,965 patients aged 18 years or older who were newly diagnosed with diabetes 2007-2011 COCI, Care density 8/9 Each year of 3 years follow-up Partly, reversed causality accounted in design and discussed in limitations Hospital admission for diabetes or cardiovascular/cerebrovascular conditions Multi-morbid patients with high- or median-COCI were less likely to be hospitalized for diabetes-related conditions than those in the low-continuity group (OR=0.86, CI: 0.77- 0.96) and (OR=0.90, CI: 0.83-0.98), respectively. For care coordination, the patients in the high- or median-care-density groups were less likely to be hospitalized for diabetes-related conditions than the patients in the low-care-density group (OR=0.84, CI: 0.76-0.93, and OR=0.91, CI:0.84-0.99).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our review shed light on an emerging consensus in terms of the direction of associations between COC and outcomes that were commonly identified in claims-based studies on healthcare use and cost. These findings emphasize the need to foster COC and to develop continuity-improving strategies, which may be potentially considered for future research: gatekeeping or managed care healthcare models, financing mechanisms for healthcare providers, data sharing and incentives for care coordination and professional collaboration [ 12 , 18 , 48 , 72 , 84 – 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced adherence is only one of the many benefits of enhancing continuity of care. A recent study showed that continuity of care was protective against polypharmacy [ 74 ] and hospitalization [ 75 ]. According to The American Heart Association/American College lifestyle guidelines, lifestyle recommendations such as exercise/physical activity, dietary modification, and reductions in weight and tobacco use have been suggested as initial forms of treatment as well as an adjunct therapy for managing hypertension [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, previous studies focused on the risk of DRPH among individual patients with diabetes and identified influencing factors largely at the individual level and only a few at the institutional and township levels. At the individual level, patients with diabetes were more likely to undergo DRPH if they were male [ 41 , 42 ], aged 65 and above [ 41 , 42 , 43 ], had low individual/household incomes [ 12 , 41 , 42 , 43 ], not taking regular physical activities [ 44 ], with higher comorbidities [ 12 , 42 , 43 , 44 ] and DCSI scores [ 41 , 43 ], had hospital admissions [ 43 ] and physician visits in the previous years [ 41 ], not enrolled in the pay-for-performance program [ 12 , 42 ], and the care had low continuity and coordination [ 41 ]. At the institutional and township levels, patients with diabetes were more likely to undergo DRPH if they received treatments in hospitals than in clinics [ 12 ], lived in the townships with lower coverage of higher education [ 12 ] and less physician density [ 43 ], lived in rural areas [ 41 , 43 ] or southern area than the capital city of Taipei [ 42 ].…”
Section: Discussionmentioning
confidence: 99%